2022
DOI: 10.1016/j.thromres.2021.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic features of Chinese pediatric patients with severe congenital protein C deficiency who first presented with purpura fulminans: A case series study and literature review

Abstract: Introduction: Purpura fulminans (PF) is a hematological emergency that can be caused by severe congenital protein C (PC) deficiency. It has been rarely reported in the Chinese population. We aimed to characterize the clinical and genetic features of Chinese pediatric patients with severe congenital PC deficiency who first presented with PF. Materials and methods: Twelve pediatric patients were diagnosed with severe congenital PC deficiency with PF, which was diagnosed based on our hospital records and previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, prenatal‐onset ICTH and/or OB have been found in PC‐deficient neonates with biallelic variants. Considering that ocular lesions were detected in two (29%) of seven PROC ‐biallelic neonatal cases in China, 45 the incidence in Japan (4/29, 14%) may recall the limit of postnatal intervention for severe neonatal PC deficiency. In Japan, APC is the sole licensed agent for acute treatment; however, it does not prevent thrombosis in heritable PC‐deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prenatal‐onset ICTH and/or OB have been found in PC‐deficient neonates with biallelic variants. Considering that ocular lesions were detected in two (29%) of seven PROC ‐biallelic neonatal cases in China, 45 the incidence in Japan (4/29, 14%) may recall the limit of postnatal intervention for severe neonatal PC deficiency. In Japan, APC is the sole licensed agent for acute treatment; however, it does not prevent thrombosis in heritable PC‐deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals heterozygous for PROC are predisposed to thrombosis when infected or distressed [7]. A case series of 12 Chinese infants revealed that all the cases with neonatal PF, except one, had a protein C level of less than 10% [8]. Heterozygous protein C deficiency is associated with less severe symptoms and is unlikely to present with arterial thrombosis [9].…”
Section: Table 1: Blood Workup At Admissionmentioning
confidence: 99%
“…Further, the possibility of obtaining a PC + PS concentrate from unused plasma fractionation intermediates rather than from plasma fractions earmarked for other products would significantly reduce manufacturing costs, favourably impacting prices for patients and National Health Systems. The clinical importance of PC and its cofactor PS has been deduced from the finding of reduced plasma levels of PC or PS in patients with congenital thrombotic disease [12,13] and in NPF where the deficiency can be caused by a lack of PC but also of PS [14].…”
Section: Introductionmentioning
confidence: 99%